2022
DOI: 10.1002/ppp3.10323
|View full text |Cite
|
Sign up to set email alerts
|

Plant awareness is linked to plant relevance: A review of educational and ethnobiological literature (1998–2020)

Abstract: Societal Impact Statement This research attempts to provide novel insights into plant awareness disparity (plant blindness), through a systematic and critical examination of the educational and ethnobiological literature. The low interest and awareness for plants is well documented in urban societies and has serious implications for biodiversity conservation and sustainable land‐use. This study is significant because it provides a comprehensive analysis of the characteristics of human‐plant relations in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 87 publications
0
25
0
1
Order By: Relevance
“…The bullet points indicate our findings. * refer to cited articles that investigate the indicated connection: *1 Balding and Wiliams (2016) *2 Colléony et al (2017) *3 Saunders et al (2006) *4 Stagg and Dillion (2022) *5 Sanders et al (2021) *6 Ford et al (2012) *7 Ives and Kendal (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bullet points indicate our findings. * refer to cited articles that investigate the indicated connection: *1 Balding and Wiliams (2016) *2 Colléony et al (2017) *3 Saunders et al (2006) *4 Stagg and Dillion (2022) *5 Sanders et al (2021) *6 Ford et al (2012) *7 Ives and Kendal (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Plant blindness was hypothesised to be inherent in the (contemporary, urban) human mindset (Wandersee & Schussler, 2001). Recently, plant blindness was found to be lower in rural communities, especially for people who collect wild plants for subsistence (Stagg & Dillon, 2022). It was also found to decline with early learning and exposure to plants (Jose et al, 2019) and in higher botany education with teaching methods based on variation theory (Sanders et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of modern indigenous communities, for example, suggest that the interaction between human and plants are related to where they live and how oral based knowledge is transferred to the next generations (Haq et al, 2022). For example, a recent literature review showed that communities in urbanised and wealthier societies are less plant aware compared with communities that live closer to nature (Pilgrim et al, 2008; Stagg & Dillon, 2022). It has been suggested that rapidly changing climates during the Palaeolithic would have resulted in subsequent vegetation changes (Bertran et al, 2013; Finlayson & Carrión, 2007; Gómez‐Olivencia et al, 2015; Jones et al, 2021), indicating to have caused population migrations (Kondo et al, 2018) to refugia (Jones et al, 2020) and biomes that offered more diverse environmental opportunities (Gavashelishvili & Tarkhnishvili, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘plant blindness’, or the more recently suggested alternative term, which we use in this paper, ‘plant awareness disparity’ (PAD) (Parsley, 2020), encompasses the idea that, compared with animals, there is a disparity of people that notice plants in their own environment (Wandersee & Schussler, 1999), resulting in the underappreciation or lack of recognition towards plants. PAD is thought to have arisen during the last century as a result of modernisation and urbanisation of many societies (Stagg & Dillon, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, a diminished potential to encounter plants in urbanised settings appears to underpin this phenomenon. Diminishing experiences with plants results in a cyclical process by reducing awareness and attention (Stagg & Dillon, 2022).…”
Section: Challenges: Contributing Factors To Common Wild Flowering Pl...mentioning
confidence: 99%